2007
DOI: 10.1142/s0192415x07005375
|View full text |Cite
|
Sign up to set email alerts
|

Application of Proteomics in Chinese Medicine Research

Abstract: Proteomics technologies can be applied to simultaneously study the function, organization, diversity, and dynamic variety of a cell or a whole tissue. The integrative approach of proteomics is in line with the holistic concept and practices of traditional Chinese medicine (TCM). In this review, the technologies of proteomics, their adoption leverages the depth and breadth of TCM research are introduced. This article presents some examples to illustrate the use of proteomics technologies in the study of pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 37 publications
(34 reference statements)
0
25
0
2
Order By: Relevance
“…Proteomics, now a day's is becoming a valuable tool for elucidating multi-target effects of complex herbal preparations, discovery of single bioactive compounds, development of active fractions, characterization of secure herbal prescriptions and eventually modified molecular diagnosis. 39 …”
Section: Genomics and Its Modified Techniquesmentioning
confidence: 99%
“…Proteomics, now a day's is becoming a valuable tool for elucidating multi-target effects of complex herbal preparations, discovery of single bioactive compounds, development of active fractions, characterization of secure herbal prescriptions and eventually modified molecular diagnosis. 39 …”
Section: Genomics and Its Modified Techniquesmentioning
confidence: 99%
“…Having the genomic data available, many new 'drug-able' targets based on transcriptomics study have been identified, opening up new insights into explanations of biological systems at a global scale. Additionally, through proteomics, we are witnessing the development of wonderful and multi-application tools for studying various signaling or mechanism systems at the level of proteins and proteinprotein interactions [20,21]. In the meantime, studies on glycol-biology and bioactive polysaccharides are making great leaps in glycomics research; similarly, studies on regulation and metabolic control of a spectrum of lipids are creating new approaches for "lipidomics".…”
Section: Omics Technologiesmentioning
confidence: 99%
“…Proteomics technologies were applied to simultaneously study the function, organization, diversity, and the dynamic variety of total or a subset of proteins at the cellular or tissue levels [21]. The current integrative approach used in proteomics is in line with the practice and holistic philosophy of traditional Chinese medicine (TCM).…”
Section: Application Of Proteomics For Research Into Traditional Herbmentioning
confidence: 99%
“…Proteomic studies have also been conducted on plants of toxic and medicinal interest, and not surprisingly plants from TCM have been the focus [138]. Two studies have been reported on the genus Scutellaria.…”
Section: Systems Toxicologymentioning
confidence: 99%